Quantum measurement enables single biomarker sensitivity in flow cytometry - J. Sabines-Chesterking; I. A. Burenkov; S. V. Polyakov (Scientific Reports, 2024)
Abstract We present the first unambiguous experimental method enabling single-fluorophore sensitivity in a flow cytometer using quantum properties of single-photon emitters. We use a quantum measurement based on the second-order coherence function to prove that the optical signal is produced by individual biomarkers traversing the interrogation volume of the flow cytometer from the first principles. This observation enables the use of the quantum toolbox for rapid detection, enumeration, and sorting of single fluorophores in large cell populations as well as a ‘photons-to-moles’ calibration of this measurement modality.